Preparation method and application of modified graphite negative electrode material for lithium ion battery
By using boric acid modified graphite material and multi-layer coated silicon carbon material in lithium batteries, the problems of high expansion rate and poor conductivity of silicon-based negative electrodes are solved, and a lithium-ion battery negative electrode material with high energy density and high rate performance is achieved.
Patent Information
- Application Number
- CN202411844193.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The large volume expansion rate of the silicon-based negative electrode in existing lithium batteries during charging causes the interface to be easily broken, and the side reactions increase, resulting in a sharp attenuation of capacity. The conductivity of silicon semiconductors is weak, and the conductivity of the composite negative electrode is low, resulting in poor rate performance.
Boric acid modified graphite material is used as the negative electrode material, and the modified graphite negative electrode material is formed by coating multiple layers of silicon carbon material, and prepared through hydrothermal reaction and calcination process to improve the conductivity and structural stability of the negative electrode.
The lithium-ion battery negative electrode material with low expansion rate, high specific capacity and high cycle stability is achieved, which significantly improves the energy density and rate performance of the battery.
Smart Images

Figure CN119324224B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a preparation method and application of a modified graphite negative electrode material for lithium ion batteries. Background Art
[0002] With the rapid development of the new energy vehicle industry, the industry and the market have put forward higher performance requirements for the power batteries used in new energy vehicles, such as hoping that the power batteries have high energy density and high safety. The energy density of the battery is mainly determined by the gram capacity of the positive and negative electrode materials. Lithium batteries usually use graphite materials as negative electrodes. The actual gram capacity of artificial graphite or natural graphite currently used in power batteries can reach 340-365mAh / g, and its actual gram capacity is close to the gram capacity upper limit of graphite materials, 372mAh / g. If the energy density of lithium batteries is to be further improved, the development of a negative electrode material system with higher gram capacity has become a must.
[0003] The most promising negative electrode material is silicon-based negative electrode. Based on silicon's unique alloying and lithium insertion mechanism, during the battery charging process, one silicon atom can alloy with 4.4 lithium atoms to achieve energy storage. The theoretical gram capacity of pure silicon can reach 4200mAh / g. By combining silicon with graphite, the gram capacity of silicon can be increased to ≥600mAh / g, thereby significantly reducing the weight of the negative electrode of the lithium battery and significantly improving the energy density of the lithium battery. However, the alloying and lithium insertion mechanism of the silicon negative electrode has the following defects: the extremely large volume expansion rate makes the expansion rate of the pure silicon negative electrode during the charging process reach 300%, the negative electrode interface is easily broken, and the interface side reactions increase, resulting in a sharp decline in the capacity of the lithium battery.
[0004] In the related art, the expansion rate of lithium batteries during charging is reduced by optimizing the structure of silicon-based negative electrodes and coating the surface. For example, a layer of artificial graphite is coated on the surface of the silicon negative electrode by ball milling to obtain a silicon-carbon composite negative electrode with a core-shell structure. However, the completely coated core-shell structure is easily broken during the repeated expansion of the silicon-based negative electrode, which in turn causes a sharp decline in the battery capacity. For example, a flexible polymer layer is used to reduce the expansion of the negative electrode, but the conductivity of the organic polymer layer is poor, and the conductivity of the silicon semiconductor is weak, so the conductivity of the composite negative electrode is low, resulting in poor rate performance of the lithium battery. Therefore, there is an urgent need for a carbon material coating method that prevents the nanostructure from being broken during the repeated expansion of silicon. Summary of the invention
[0005] The present invention provides a preparation method and application of a modified graphite negative electrode material for a lithium ion battery to solve the deficiencies in the related art.
[0006] According to a first aspect of an embodiment of the present disclosure, there is provided a method for preparing a modified graphite negative electrode material for a lithium ion battery, the preparation method comprising the following steps:
[0007] Step 1: preparing a boric acid-modified graphite material; mixing the boric acid-modified graphite material with a binder and a conductive agent to obtain a first negative electrode material;
[0008] Step 2: preparing a first silicon-carbon material, applying a slurry containing the first silicon-carbon material onto the first negative electrode material, and after curing, forming a first coating on the first negative electrode material;
[0009] Step 3: prepare a second silicon-carbon material, apply a slurry containing the second silicon-carbon material on the first coating, and after curing, form a second coating on the first coating to obtain the modified graphite negative electrode material for lithium-ion batteries.
[0010] In one aspect of the disclosed embodiments, in the modified graphite negative electrode material for lithium ion batteries, the mass ratio of the first silicon-carbon material to the second silicon-carbon material is selected from (0.25-0.65): 1. Preferably, in the modified graphite negative electrode material for lithium ion batteries, the mass ratio of the first silicon-carbon material to the second silicon-carbon material is selected from (0.35-0.55): 1.
[0011] In one aspect of the embodiments of the present disclosure, the boric acid-modified graphite material is obtained by the following preparation method:
[0012] Step 1-a: adding graphite raw material and boric acid to acetic acid, stirring and then subjecting to a hydrothermal reaction process; obtaining the product of step 1-a;
[0013] Step 2-a: drying the product obtained in step 1-a, and then calcining the product to obtain a crude boric acid-modified graphite material;
[0014] Step 3-a: subjecting the crude boric acid-modified graphite material to a post-treatment process to obtain the boric acid-modified graphite material.
[0015] In one aspect of the embodiments of the present disclosure, in step 1-a, the hydrothermal reaction process is: subjecting the stirred acetic acid containing graphite raw material and boric acid to a hydrothermal reaction at 160° C.-200° C., and the reaction time is 6-12 hours.
[0016] In one aspect of the disclosed embodiment, in step 2-a, the calcination process is: in a nitrogen atmosphere, triethylamine is introduced, and the temperature is raised from room temperature to 650°C-850°C within 3-6 hours, calcined for 3-6 hours, and then naturally cooled to room temperature.
[0017] In one aspect of the embodiments of the present disclosure, in step 3-a, the post-treatment process is: washing, drying and grinding the crude boric acid-modified graphite material, and then passing it through a 160-200 mesh sieve to obtain the boric acid-modified graphite material.
[0018] In one aspect of the disclosed embodiment, in step 1-a, the mass ratio of the graphite raw material to boric acid is selected from 1:(0.05-0.25). Preferably, in step 1-a, the mass ratio of the graphite raw material to boric acid is selected from 1:(0.08-0.15).
[0019] Specifically, in one aspect of the embodiments of the present disclosure, the boric acid-modified graphite material is obtained by the following preparation method:
[0020] Step 1-a: 24 g of graphite raw material and 2.4 g of boric acid were added to 50 mL of acetic acid, stirred, and subjected to hydrothermal reaction at 180° C. for 8 h to obtain the product of step 1-a;
[0021] Step 2-a: drying the product obtained in step 1-a in an oven at 60°C, placing it in a high-temperature tube furnace, introducing 25 mL of triethylamine in a nitrogen atmosphere, heating from room temperature to 750°C within 4 hours, calcining for 5 hours, and then naturally cooling to room temperature to obtain a crude boric acid-modified graphite material;
[0022] Step 3-a: Wash, dry and grind the crude boric acid-modified graphite material, and then pass it through a 200-mesh sieve to obtain the boric acid-modified graphite material.
[0023] In one aspect of the embodiments of the present disclosure, the first silicon-carbon material is obtained by the following preparation method:
[0024] Step 1-b: preparing ZIF-67 material;
[0025] Step 2-b: adding silicon nanoparticles to water, then adding the ZIF-67 material and glucose, stirring for 0.5-3h, and then slowly adding ethanol to obtain a dispersion;
[0026] Step 3-b: leaving the dispersion to stand for 4-12 hours and then drying to obtain a first precursor;
[0027] Step 4-b: subjecting the first precursor to a calcination process, and then subjecting the calcined product to acid washing to obtain the first silicon-carbon material.
[0028] In one aspect of the embodiments of the present disclosure, the ZIF-67 material is obtained by the following preparation method:
[0029] Step 1-c: dissolving the cobalt salt and 2-methylimidazole in methanol respectively to obtain a methanol solution containing the cobalt salt and a methanol solution containing 2-methylimidazole;
[0030] Step 2-c: stirring the methanol solution containing the cobalt salt, then adding the methanol solution containing 2-methylimidazole, continuing to stir for 2-6 hours, and then standing for 4-12 hours to obtain a purple solution;
[0031] Step 3-c: Filter, separate, wash and dry the purple solution to obtain the ZIF-67 material.
[0032] In one aspect of the embodiments of the present disclosure, the second silicon-carbon material is obtained by the following preparation method:
[0033] Step 1-d: preparing ZIF-90 material;
[0034] Step 2-d: adding silicon nanoparticles to water, then adding the ZIF-90 material and polyvinyl alcohol, stirring for 0.5-3h, and then slowly adding ethanol to obtain a dispersion;
[0035] Step 3-d: leaving the dispersion to stand for 4-12 hours and then drying to obtain a second precursor;
[0036] Step 4-d: subjecting the second precursor to a calcination process, and then subjecting the calcined product to acid washing to obtain the second silicon-carbon material.
[0037] In one aspect of the embodiments of the present disclosure, the ZIF-90 material is obtained by the following preparation method:
[0038] Step 1-e: dissolving the zinc salt in methanol to obtain a methanol solution containing the zinc salt, then adding trimethylamine and 2-formyl imidazole, stirring at 65° C.-80° C., and heating under reflux for 1-3 h;
[0039] Step 2-e: The solution heated to reflux is further stirred at room temperature for 1-3 hours, and then water is added to obtain a precipitate;
[0040] Step 3-e: The precipitate obtained in step 2-e is washed and dried to obtain the ZIF-90 material.
[0041] In one aspect of the embodiments of the present disclosure, in step 2-b, the mass ratio of the ZIF-67 material and the silicon nanoparticles is selected from (0.5-0.75):1.
[0042] In one aspect of the embodiments of the present disclosure, in step 2-d, the mass ratio of the ZIF-90 material and the silicon nanoparticles is selected from (0.65-0.9):1.
[0043] In one aspect of the embodiments of the present disclosure, in step 2-b, the mass ratio of glucose to silicon nanoparticles is selected from (2-3.5):1.
[0044] In one aspect of the embodiments of the present disclosure, in step 2-d, the mass ratio of the polyvinyl alcohol to the silicon nanoparticles is selected from (1.5-2.5):1.
[0045] In one aspect of the embodiments of the present disclosure, the silicon nanoparticles have an average particle size of 75-150 nm.
[0046] In one aspect of the embodiments of the present disclosure, the cobalt salt may be selected from cobalt nitrate hexahydrate, but is not limited thereto.
[0047] In one aspect of the embodiments of the present disclosure, the zinc salt may be selected from zinc nitrate hexahydrate, but is not limited thereto.
[0048] In one aspect of the embodiments of the present disclosure, in step 4-b, the calcination process is: under a nitrogen atmosphere, the first precursor is heated from room temperature to 400°C-550°C within 2-4 hours, then maintained at this temperature for 3-5 hours, then heated to 800°C-950°C within 1-3 hours, and then maintained at this temperature for 2-4 hours; then naturally cooled to room temperature.
[0049] In one aspect of the embodiments of the present disclosure, in step 4-d, the calcination process is: under a nitrogen atmosphere, the second precursor is heated from room temperature to 300°C-400°C within 2-4 hours, then maintained at this temperature for 3-5 hours, then heated to 700°C-850°C within 1-3 hours, and then maintained at this temperature for 2-4 hours; then naturally cooled to room temperature.
[0050] In one aspect of the disclosed embodiment, in step 4-b, a 2 mol / L hydrochloric acid solution is used for pickling, but the invention is not limited thereto.
[0051] In one aspect of the embodiments of the present disclosure, in step 4-d, 2 mol / L hydrochloric acid solution is used for pickling, but it is not limited thereto.
[0052] According to a second aspect of an embodiment of the present disclosure, a negative electrode plate is provided, comprising a negative electrode current collector and a negative electrode material layer coated on the negative electrode current collector; the negative electrode material layer comprises a modified graphite negative electrode material obtained by the aforementioned preparation method.
[0053] According to a third aspect of the embodiments of the present disclosure, a lithium-ion battery is provided, comprising a positive electrode plate, an electrolyte, a separator and the negative electrode plate mentioned above.
[0054] The technical solution provided by the embodiments of the present disclosure may have the following beneficial effects:
[0055] It can be seen from the above embodiments that the present disclosure provides a boric acid-modified graphite negative electrode material containing silicon-carbon material with low expansion ratio, high specific capacity and high cycle stability.
[0056] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.
[0058] Figure 1 is a SEM image of the first silicon-carbon material of Example 1.
[0059] Figure 2 is a SEM image of the first silicon-carbon material of Example 6.
[0060] Figure 3 is a SEM image of the first silicon-carbon material of Example 7.
[0061] Figure 4 3 is an XRD image of the first silicon-carbon material of Example 1.
[0062] Figure 5 is a SEM image of the unmodified graphite material in Example 1.
[0063] Figure 6 : is a SEM image of the boric acid-modified graphite material obtained in Example 1. DETAILED DESCRIPTION
[0064] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0065] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0066] In this article, the terms "comprises", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.
[0067] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0068] Unless otherwise specified, the terms used in this disclosure have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this disclosure).
[0069] The term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely and an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values are sometimes presented in this article in a range format. It should be understood that such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values explicitly designated as range limits, but also all individual numerical values or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.
[0070] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0071] negative electrode:
[0072] In some embodiments of the present disclosure, the negative electrode includes a negative electrode sheet, which includes a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector, wherein the negative electrode material layer includes the modified graphite negative electrode material provided by the present disclosure.
[0073] The material of the negative electrode current collector of the present disclosure is not particularly limited. In some embodiments of the present disclosure, the negative electrode current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and a combination thereof.
[0074] In some embodiments of the present disclosure, the negative electrode current collector may be selected from copper foil.
[0075] In some embodiments of the present disclosure, the negative electrode material layer includes a negative electrode active material, a conductive agent, and a binder; wherein the negative electrode active material is the modified graphite negative electrode material provided by the present disclosure.
[0076] In some embodiments of the present disclosure, the negative electrode active material is the key to ensuring that the negative electrode has good charge and discharge performance. The negative electrode active material of the present disclosure includes a boric acid-modified graphite material, a first coating coated on the boric acid-modified graphite material, and a second coating coated on the first coating.
[0077] In some embodiments of the present disclosure, based on the total weight of the negative electrode active material, the weight percentage of the first coating layer is 1-5%, but is not limited thereto.
[0078] In some embodiments of the present disclosure, based on the total weight of the negative electrode active material, the weight percentage of the second coating layer is 2-10%, but is not limited thereto.
[0079] In some embodiments of the present disclosure, the negative electrode active material is prepared by the following preparation method:
[0080] Step 1: preparing a boric acid-modified graphite material;
[0081] Step 2: preparing a first silicon-carbon material, applying a slurry containing the first silicon-carbon material on the boric acid-modified graphite material, and forming a first coating after curing to obtain a graphite material containing the first coating;
[0082] Step 3: prepare a second silicon-carbon material, apply a slurry containing the second silicon-carbon material on the graphite material containing the first coating, and after curing, form a second coating on the first coating to obtain a modified graphite negative electrode material for lithium-ion batteries.
[0083] In some embodiments of the present disclosure, the negative electrode material layer may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0084] In some embodiments of the present disclosure, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.
[0085] In some embodiments of the present disclosure, the negative electrode material layer includes a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0086] positive electrode:
[0087] In some embodiments of the present disclosure, the positive electrode includes a positive electrode sheet, which includes a positive electrode current collector and a positive electrode active material layer disposed on the current collector. The positive electrode active material includes a compound that reversibly embeds and deintercalates lithium ions. The positive electrode active material may include a composite oxide containing lithium and at least one element selected from cobalt, manganese and nickel. The specific types of positive electrode active materials are not subject to specific restrictions and can be selected according to needs. The positive electrode active material is selected from at least one of lithium cobalt oxide LiCoO2 (LCO), lithium nickel manganese cobalt ternary material (NCM), lithium iron phosphate, and lithium manganese oxide. They can be used alone or in any combination of two or more.
[0088] In other embodiments of the present disclosure, the positive electrode current collector may be selected from aluminum foil.
[0089] In some embodiments of the present disclosure, the positive electrode active material may have a coating on the surface. The compound for the coating may be amorphous or crystalline, and the coating element contained in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating may be applied by any method as long as the method does not adversely affect the performance of the positive electrode active material. For example, the method may include any coating method well known to those of ordinary skill in the art, such as spraying, dipping, etc.
[0090] In some embodiments of the present disclosure, the positive electrode active material layer further includes a binder, and optionally also includes a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.
[0091] In some embodiments of the present disclosure, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.
[0092] In some embodiments of the present disclosure, non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.
[0093] Diaphragm:
[0094] In some embodiments of the present disclosure, the lithium ion battery and electrochemical device of the present disclosure are provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present disclosure are not particularly limited, and it can be any technology disclosed in the prior art.
[0095] In some embodiments of the present disclosure, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0096] In some embodiments of the present disclosure, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.
[0097] Electrolyte:
[0098] The lithium-ion batteries and electrochemical devices of the present disclosure also include an electrolyte.
[0099] In some embodiments, the electrolyte includes a lithium salt and a solvent.
[0100] In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB), or lithium di(oxalatoborate) LiBF2(C2O4) (LiDFOB).
[0101] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0102] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.
[0103] Lithium-ion battery:
[0104] In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure includes the above-mentioned positive electrode sheet, negative electrode sheet, separator, electrolyte, etc., but is not limited thereto.
[0105] In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure is made by stacking the above-mentioned positive and negative electrode sheets.
[0106] In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0107] In some embodiments, the present disclosure further provides a battery module. The battery module includes the above-mentioned lithium-ion battery. The battery module of the present disclosure uses the above-mentioned lithium-ion battery, and therefore has at least the same advantages as the lithium-ion battery. The number of lithium-ion batteries contained in the battery module of the present disclosure can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0108] In some embodiments, the present disclosure further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0109] Device:
[0110] The present disclosure also provides a device, which includes at least one of the above-mentioned lithium-ion battery, battery module or battery pack.
[0111] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or battery module may be used.
[0112] In other embodiments, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be thin and light, and a lithium-ion battery may be used as a power source.
[0113] The present disclosure is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure.
[0114] Embodiment and comparative example:
[0115] Embodiment 1 comprises the following steps:
[0116] 1. Preparation of ZIF-67 material:
[0117] 1.75 g of cobalt nitrate hexahydrate and 7.85 g of 2-methylimidazole were respectively dissolved in 50 mL of methanol, and completely dissolved after ultrasonic treatment to obtain a methanol solution containing cobalt nitrate hexahydrate and a methanol solution containing 2-methylimidazole;
[0118] The methanol solution containing cobalt nitrate hexahydrate was stirred, and then the methanol solution containing 2-methylimidazole was added, and the stirring was continued for 4 hours, and then allowed to stand for 10 hours to obtain a purple solution;
[0119] The purple solution was filtered, separated, washed three times with anhydrous ethanol and deionized water, and then dried to obtain the ZIF-67 material.
[0120] 2. Preparation of ZIF-90 material:
[0121] Dissolve 1.5 g of zinc nitrate hexahydrate in 50 mL of methanol, then add 1.5 mL of trimethylamine and 1 g of 2-formyl imidazole, keep stirring at 75 ° C, and heat under reflux for 2 h;
[0122] The solution after heating to reflux was stirred at room temperature for 1.5 h, and then 150 mL of deionized water was added to obtain a precipitate;
[0123] The obtained precipitate was washed and dried to obtain ZIF-90 material.
[0124] 3. Preparation of the first silicon-carbon material:
[0125] 1 g of silicon nanoparticles (average particle size of 80 nm, purity of 99.9%, purchased from Shanghai Naio Nano Technology Co., Ltd.) was weighed and added to 100 mL of deionized water, and then 0.6 g of the prepared ZIF-67 material and 3 g of glucose were added, stirred for 1.5 h, and then 60 mL of ethanol was slowly added to obtain a dispersion;
[0126] After the dispersion was allowed to stand for 8 hours, it was dried at 60° C. to obtain a first precursor;
[0127] In a nitrogen atmosphere, the first precursor was heated from room temperature to 450°C within 3 hours, then maintained at 450°C for 4 hours, then heated to 900°C within 2 hours, and then maintained at 900°C for 3 hours; then naturally cooled to room temperature; and then the calcined product was acid-washed with a 2 mol / L hydrochloric acid solution to obtain a first silicon-carbon material. The SEM image of the first silicon-carbon material of Example 1 is shown in FIG. Figure 1 As shown; the XRD image of the first silicon-carbon material of Example 1 is as shown Figure 4 As shown, from Figure 4 It can be seen that the first silicon-carbon material of Example 1 contains silicon and carbon.
[0128] 4. Preparation of the second silicon-carbon material:
[0129] 1 g of silicon nanoparticles (average particle size of 80 nm, purity of 99.9%, purchased from Shanghai Naio Nano Technology Co., Ltd.) was weighed and added to 100 mL of deionized water, and then 0.8 g of the prepared ZIF-90 material and 2 g of polyvinyl alcohol (PVA1799) were added, stirred for 1.5 h, and then 75 mL of ethanol was slowly added to obtain a dispersion;
[0130] The dispersion was allowed to stand for 10 hours and then dried to obtain a second precursor;
[0131] Under a nitrogen atmosphere, the second precursor is heated from room temperature to 300°C-400°C within 2-4 hours, then maintained at this temperature for 3-5 hours, then heated to 700°C-850°C within 1-3 hours, and then maintained at this temperature for 2-4 hours; then naturally cooled to room temperature; and then the calcined product is pickled with a 2 mol / L hydrochloric acid solution to obtain a second silicon-carbon material.
[0132] 5. Preparation of boric acid modified graphite material:
[0133] 24 g of graphite raw material (natural graphite, the SEM image of which is shown in Figure 5 As shown in the figure, 2.4 g of boric acid were added into 50 mL of acetic acid, and after stirring, a hydrothermal reaction was carried out at 180° C. for 8 h to obtain an intermediate product;
[0134] The intermediate product was dried in an oven at 60°C, placed in a high-temperature tube furnace, introduced with 25 mL of triethylamine under a nitrogen atmosphere, heated from room temperature to 750°C within 4 hours, calcined for 5 hours, and then naturally cooled to room temperature to obtain a crude boric acid-modified graphite material;
[0135] The crude boric acid-modified graphite material is washed, dried and ground, and then passed through a 200-mesh sieve to obtain a boric acid-modified graphite material. Figure 6 As shown, relative to Figure 5 The unmodified graphite material shown, the boric acid-modified graphite material obtained in Example 1 has a large number of gaps and wrinkles.
[0136] 6. Preparation of negative electrode materials:
[0137] Weigh 9.5g of boric acid-modified graphite material, and fully stir and mix the boric acid-modified graphite material, conductive agent SP (conductive carbon black), and binder styrene-butadiene rubber (SBR) in a proper amount of deionized water at a weight ratio of 95:2.5:2.5 to form a uniform negative electrode slurry. Apply the slurry on the negative electrode current collector copper foil, dry it, and cold press it to obtain the first negative electrode material layer;
[0138] Weigh 0.4 g of the prepared first silicon-carbon material, and mix it with a conductive agent SP (conductive carbon black), a thickener sodium carboxymethyl cellulose (CMC), and a binder styrene-butadiene rubber (SBR) in a weight ratio of 8:0.5:0.5:1 in an appropriate amount of 60% ethanol solution, and then coat it on the first negative electrode material layer; after drying, a negative electrode material layer including the first coating is obtained.
[0139] Weigh 0.85 g of the prepared second silicon-carbon material, mix it with a conductive agent SP (conductive carbon black), a thickener sodium carboxymethyl cellulose (CMC), and a binder styrene-butadiene rubber (SBR) in a weight ratio of 8:0.5:0.5:1 in an appropriate amount of NMP, stir it thoroughly and apply it on the first coating; after drying, the negative electrode of Example 1 is obtained.
[0140] 7. Preparation of lithium-ion batteries:
[0141] The positive electrode active material LiMn2O4, the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96:2:2, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain the positive electrode active material layer, and then cut, slit, and weld the pole ears to obtain the positive electrode.
[0142] The positive electrode, the isolation film (using a PP / PE / PP three-layer composite separator), and the negative electrode are stacked in order, so that the isolation film is between the positive electrode plate and the negative electrode plate to play an isolating role, to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and an electrolyte (containing 1 mol / L of lithium hexafluorophosphate ethylene carbonate) is injected into the bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Example 1 is completed.
[0143] The steps of Example 2 are basically the same as those of Example 1, except that when preparing the boric acid-modified graphite material, the amount of boric acid used is 2 g.
[0144] The steps of Example 3 are basically the same as those of Example 1, except that when preparing the boric acid-modified graphite material, the amount of boric acid used is 3.6 g.
[0145] The steps of Example 4 are basically the same as those of Example 1, except that when preparing the boric acid-modified graphite material, the amount of boric acid used is 0.85 g.
[0146] The steps of Example 5 are basically the same as those of Example 1, except that when preparing the boric acid-modified graphite material, the amount of boric acid used is 6 g.
[0147] Embodiment 6 comprises the following steps:
[0148] 1. Preparation of ZIF-90 material:
[0149] Dissolve 1.5 g of zinc nitrate hexahydrate in 50 mL of methanol, then add 1.5 mL of trimethylamine and 1 g of 2-formyl imidazole, keep stirring at 75 ° C, and heat under reflux for 2 h;
[0150] The solution after heating to reflux was stirred at room temperature for 1.5 h, and then 150 mL of deionized water was added to obtain a precipitate;
[0151] The obtained precipitate was washed and dried to obtain ZIF-90 material.
[0152] 2. Preparation of the first silicon-carbon material:
[0153] 1 g of silicon nanoparticles (average particle size of 80 nm, purity of 99.9%, purchased from Shanghai Naio Nano Technology Co., Ltd.) was weighed and added to 100 mL of deionized water, and then 0.6 g of the prepared ZIF-90 material and 3 g of glucose were added, stirred for 1.5 h, and then 60 mL of ethanol was slowly added to obtain a dispersion;
[0154] After the dispersion was allowed to stand for 8 hours, it was dried at 60° C. to obtain a first precursor;
[0155] In a nitrogen atmosphere, the first precursor was heated from room temperature to 450°C within 3 hours, then maintained at 450°C for 4 hours, then heated to 900°C within 2 hours, and then maintained at 900°C for 3 hours; then naturally cooled to room temperature; and then the calcined product was acid-washed with a 2 mol / L hydrochloric acid solution to obtain a first silicon-carbon material. The SEM image of the first silicon-carbon material of Example 6 is shown in FIG. Figure 2 shown.
[0156] 3. Preparation of the second silicon-carbon material:
[0157] 1 g of silicon nanoparticles (average particle size of 80 nm, purity of 99.9%, purchased from Shanghai Naio Nano Technology Co., Ltd.) was weighed and added to 100 mL of deionized water, and then 0.8 g of the prepared ZIF-90 material and 2 g of polyvinyl alcohol (PVA1799) were added, stirred for 1.5 h, and then 75 mL of ethanol was slowly added to obtain a dispersion;
[0158] The dispersion was allowed to stand for 10 hours and then dried to obtain a second precursor;
[0159] Under a nitrogen atmosphere, the second precursor is heated from room temperature to 300°C-400°C within 2-4 hours, then maintained at this temperature for 3-5 hours, then heated to 700°C-850°C within 1-3 hours, and then maintained at this temperature for 2-4 hours; then naturally cooled to room temperature; and then the calcined product is pickled with a 2 mol / L hydrochloric acid solution to obtain a second silicon-carbon material.
[0160] 4. Preparation of boric acid modified graphite material:
[0161] 24 g of graphite raw material (natural graphite) and 2.4 g of boric acid were added to 50 mL of acetic acid, stirred, and subjected to hydrothermal reaction at 180° C. for 8 h to obtain an intermediate product;
[0162] The intermediate product was dried in an oven at 60°C, placed in a high-temperature tube furnace, introduced with 25 mL of triethylamine under a nitrogen atmosphere, heated from room temperature to 750°C within 4 hours, calcined for 5 hours, and then naturally cooled to room temperature to obtain a crude boric acid-modified graphite material;
[0163] The crude boric acid-modified graphite material is washed, dried, and ground, and then passed through a 200-mesh sieve to obtain a boric acid-modified graphite material.
[0164] 5. Preparation of negative electrode materials:
[0165] Weigh 9.5g of boric acid-modified graphite material, and fully stir and mix the boric acid-modified graphite material, conductive agent SP (conductive carbon black), and binder styrene-butadiene rubber (SBR) in a proper amount of deionized water at a weight ratio of 95:2.5:2.5 to form a uniform negative electrode slurry. Apply the slurry on the negative electrode current collector copper foil, dry it, and cold press it to obtain the first negative electrode material layer;
[0166] Weigh 0.4 g of the prepared first silicon-carbon material, and mix it with a conductive agent SP (conductive carbon black), a thickener sodium carboxymethyl cellulose (CMC), and a binder styrene-butadiene rubber (SBR) in a weight ratio of 8:0.5:0.5:1 in an appropriate amount of 60% ethanol solution, and then coat it on the first negative electrode material layer; after drying, a negative electrode material layer including the first coating is obtained.
[0167] Weigh 0.85 g of the prepared second silicon-carbon material, mix it with a conductive agent SP (conductive carbon black), a thickener sodium carboxymethyl cellulose (CMC), and a binder styrene-butadiene rubber (SBR) in a weight ratio of 8:0.5:0.5:1 in an appropriate amount of NMP, stir it thoroughly and apply it on the first coating; after drying, the negative electrode of Example 6 is obtained.
[0168] 6. Preparation of lithium-ion batteries:
[0169] The positive electrode active material LiMn2O4, the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96:2:2, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain the positive electrode active material layer, and then cut, slit, and weld the pole ears to obtain the positive electrode.
[0170] The positive electrode, the isolation film (using a PP / PE / PP three-layer composite separator), and the negative electrode are stacked in order, so that the isolation film is between the positive electrode plate and the negative electrode plate to play an isolating role, to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and the electrolyte (containing 1 mol / L of lithium hexafluorophosphate ethylene carbonate) is injected into the bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Example 6 is completed.
[0171] The main difference between Example 6 and Example 1 is that the first silicon-carbon material in Example 6 is prepared by using ZIF-90 as a template.
[0172] Embodiment 7 comprises the following steps:
[0173] 1. Preparation of ZIF-8 material:
[0174] 1.10 g of zinc nitrate hexahydrate and 2.35 g of 2-methylimidazole were respectively dissolved in 50 mL of methanol, and completely dissolved after ultrasonic treatment to obtain a methanol solution containing cobalt nitrate hexahydrate and a methanol solution containing 2-methylimidazole;
[0175] The methanol solution containing cobalt nitrate hexahydrate was stirred, and then the methanol solution containing 2-methylimidazole was added, and stirring was continued for 24 hours. The resulting solution was centrifuged and washed with methanol to obtain a white precipitate, and the white precipitate was dried to obtain a ZIF-8 material.
[0176] 2. Preparation of ZIF-90 material:
[0177] Dissolve 1.5 g of zinc nitrate hexahydrate in 50 mL of methanol, then add 1.5 mL of trimethylamine and 1 g of 2-formyl imidazole, keep stirring at 75 ° C, and heat under reflux for 2 h;
[0178] The solution after heating to reflux was stirred at room temperature for 1.5 h, and then 150 mL of deionized water was added to obtain a precipitate;
[0179] The obtained precipitate was washed and dried to obtain ZIF-90 material.
[0180] 3. Preparation of the first silicon-carbon material:
[0181] 1 g of silicon nanoparticles (average particle size of 80 nm, purity of 99.9%, purchased from Shanghai Naio Nano Technology Co., Ltd.) was weighed and added to 100 mL of deionized water, and then 0.6 g of the prepared ZIF-8 material and 3 g of glucose were added, stirred for 1.5 h, and then 60 mL of ethanol was slowly added to obtain a dispersion;
[0182] After the dispersion was allowed to stand for 8 hours, it was dried at 60° C. to obtain a first precursor;
[0183] In a nitrogen atmosphere, the first precursor was heated from room temperature to 450°C within 3 hours, then maintained at 450°C for 4 hours, then heated to 900°C within 2 hours, and then maintained at 900°C for 3 hours; then naturally cooled to room temperature; and then the calcined product was acid-washed with a 2 mol / L hydrochloric acid solution to obtain a first silicon-carbon material. The SEM image of the first silicon-carbon material of Example 7 is shown in FIG. Figure 3 shown.
[0184] 4. Preparation of the second silicon-carbon material:
[0185] 1 g of silicon nanoparticles (average particle size of 80 nm, purity of 99.9%, purchased from Shanghai Naio Nano Technology Co., Ltd.) was weighed and added to 100 mL of deionized water, and then 0.8 g of the prepared ZIF-90 material and 2 g of polyvinyl alcohol (PVA1799) were added, stirred for 1.5 h, and then 75 mL of ethanol was slowly added to obtain a dispersion;
[0186] The dispersion was allowed to stand for 10 hours and then dried to obtain a second precursor;
[0187] Under a nitrogen atmosphere, the second precursor is heated from room temperature to 300°C-400°C within 2-4 hours, then maintained at this temperature for 3-5 hours, then heated to 700°C-850°C within 1-3 hours, and then maintained at this temperature for 2-4 hours; then naturally cooled to room temperature; and then the calcined product is pickled with a 2 mol / L hydrochloric acid solution to obtain a second silicon-carbon material.
[0188] 5. Preparation of boric acid modified graphite material:
[0189] 24 g of graphite raw material (natural graphite) and 2.4 g of boric acid were added to 50 mL of acetic acid, stirred, and subjected to hydrothermal reaction at 180° C. for 8 h to obtain an intermediate product;
[0190] The intermediate product was dried in an oven at 60°C, placed in a high-temperature tube furnace, introduced with 25 mL of triethylamine under a nitrogen atmosphere, heated from room temperature to 750°C within 4 hours, calcined for 5 hours, and then naturally cooled to room temperature to obtain a crude boric acid-modified graphite material;
[0191] The crude boric acid-modified graphite material is washed, dried, and ground, and then passed through a 200-mesh sieve to obtain a boric acid-modified graphite material.
[0192] 6. Preparation of negative electrode materials:
[0193] Weigh 9.5g of boric acid-modified graphite material, and fully stir and mix the boric acid-modified graphite material, conductive agent SP (conductive carbon black), and binder styrene-butadiene rubber (SBR) in a proper amount of deionized water at a weight ratio of 95:2.5:2.5 to form a uniform negative electrode slurry. Apply the slurry on the negative electrode current collector copper foil, dry it, and cold press it to obtain the first negative electrode material layer;
[0194] Weigh 0.4 g of the prepared first silicon-carbon material, and mix it with a conductive agent SP (conductive carbon black), a thickener sodium carboxymethyl cellulose (CMC), and a binder styrene-butadiene rubber (SBR) in a weight ratio of 8:0.5:0.5:1 in an appropriate amount of 60% ethanol solution, and then coat it on the first negative electrode material layer; after drying, a negative electrode material layer including the first coating is obtained.
[0195] Weigh 0.85 g of the prepared second silicon-carbon material, mix it with a conductive agent SP (conductive carbon black), a thickener sodium carboxymethyl cellulose (CMC), and a binder styrene-butadiene rubber (SBR) in a weight ratio of 8:0.5:0.5:1 in an appropriate amount of NMP, stir it thoroughly and apply it on the first coating; after drying, the negative electrode of Example 7 is obtained.
[0196] 7. Preparation of lithium-ion batteries:
[0197] The positive electrode active material LiMn2O4, the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96:2:2, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain the positive electrode active material layer, and then cut, slit, and weld the pole ears to obtain the positive electrode.
[0198] The positive electrode, the isolation film (using a PP / PE / PP three-layer composite separator), and the negative electrode are stacked in order, so that the isolation film is between the positive electrode plate and the negative electrode plate to play an isolating role, to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and the electrolyte (containing 1 mol / L of lithium hexafluorophosphate in ethylene carbonate) is injected into the bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Example 7 is completed.
[0199] The main difference between Example 7 and Example 1 is that the first silicon-carbon material in Example 7 is prepared by using ZIF-8 as a template.
[0200] Comparative Example 1:
[0201] 1. Preparation of ZIF-67 material:
[0202] 1.75 g of cobalt nitrate hexahydrate and 7.85 g of 2-methylimidazole were respectively dissolved in 50 mL of methanol, and completely dissolved after ultrasonic treatment to obtain a methanol solution containing cobalt nitrate hexahydrate and a methanol solution containing 2-methylimidazole;
[0203] The methanol solution containing cobalt nitrate hexahydrate was stirred, and then the methanol solution containing 2-methylimidazole was added, and the stirring was continued for 4 hours, and then allowed to stand for 10 hours to obtain a purple solution;
[0204] The purple solution was filtered, separated, washed three times with anhydrous ethanol and deionized water, and then dried to obtain the ZIF-67 material.
[0205] 2. Preparation of ZIF-90 material:
[0206] Dissolve 1.5 g of zinc nitrate hexahydrate in 50 mL of methanol, then add 1.5 mL of trimethylamine and 1 g of 2-formyl imidazole, keep stirring at 75 ° C, and heat under reflux for 2 h;
[0207] The solution after heating to reflux was stirred at room temperature for 1.5 h, and then 150 mL of deionized water was added to obtain a precipitate;
[0208] The obtained precipitate was washed and dried to obtain ZIF-90 material.
[0209] 3. Preparation of the first silicon-carbon material:
[0210] 1 g of silicon nanoparticles (average particle size of 80 nm, purity of 99.9%, purchased from Shanghai Naio Nano Technology Co., Ltd.) was weighed and added to 100 mL of deionized water, and then 0.6 g of the prepared ZIF-67 material and 3 g of glucose were added, stirred for 1.5 h, and then 60 mL of ethanol was slowly added to obtain a dispersion;
[0211] After the dispersion was allowed to stand for 8 hours, it was dried at 60° C. to obtain a first precursor;
[0212] Under a nitrogen atmosphere, the first precursor was heated from room temperature to 450°C within 3 hours, then maintained at 450°C for 4 hours, then heated to 900°C within 2 hours, and then maintained at 900°C for 3 hours; then naturally cooled to room temperature; and then the calcined product was pickled with a 2 mol / L hydrochloric acid solution to obtain a first silicon-carbon material.
[0213] 4. Preparation of the second silicon-carbon material:
[0214] 1 g of silicon nanoparticles (average particle size of 80 nm, purity of 99.9%, purchased from Shanghai Naio Nano Technology Co., Ltd.) was weighed and added to 100 mL of deionized water, and then 0.8 g of the prepared ZIF-90 material and 2 g of polyvinyl alcohol (PVA1799) were added, stirred for 1.5 h, and then 75 mL of ethanol was slowly added to obtain a dispersion;
[0215] The dispersion was allowed to stand for 10 hours and then dried to obtain a second precursor;
[0216] Under a nitrogen atmosphere, the second precursor is heated from room temperature to 300°C-400°C within 2-4 hours, then maintained at this temperature for 3-5 hours, then heated to 700°C-850°C within 1-3 hours, and then maintained at this temperature for 2-4 hours; then naturally cooled to room temperature; and then the calcined product is pickled with a 2 mol / L hydrochloric acid solution to obtain a second silicon-carbon material.
[0217] 5. Preparation of negative electrode materials:
[0218] Weigh 9.5g of graphite raw material (natural graphite), stir and mix the graphite raw material, conductive agent SP (conductive carbon black), and adhesive styrene butadiene rubber (SBR) in a weight ratio of 95:2.5:2.5 in an appropriate amount of deionized water to form a uniform negative electrode slurry. Apply the slurry on the negative electrode current collector copper foil, dry and cold press to obtain the first negative electrode material layer;
[0219] Weigh 0.4 g of the prepared first silicon-carbon material, and mix it with a conductive agent SP (conductive carbon black), a thickener sodium carboxymethyl cellulose (CMC), and a binder styrene-butadiene rubber (SBR) in a weight ratio of 8:0.5:0.5:1 in an appropriate amount of 60% ethanol solution, and then coat it on the first negative electrode material layer; after drying, a negative electrode material layer including the first coating is obtained.
[0220] Weigh 0.85 g of the prepared second silicon-carbon material, mix it with a conductive agent SP (conductive carbon black), a thickener sodium carboxymethyl cellulose (CMC), and a binder styrene-butadiene rubber (SBR) in a weight ratio of 8:0.5:0.5:1 in an appropriate amount of NMP, stir it thoroughly and apply it on the first coating; after drying, the negative electrode of Comparative Example 1 is obtained.
[0221] 6. Preparation of lithium-ion batteries:
[0222] The positive electrode active material LiMn2O4, the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96:2:2, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain the positive electrode active material layer, and then cut, slit, and weld the pole ears to obtain the positive electrode.
[0223] The positive electrode, the isolation film (using a PP / PE / PP three-layer composite separator), and the negative electrode are stacked in order, so that the isolation film is between the positive electrode plate and the negative electrode plate to play an isolating role, to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and an electrolyte (containing 1 mol / L of lithium hexafluorophosphate in ethylene carbonate) is injected into the bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Comparative Example 1 is completed.
[0224] The main difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, boric acid is not used to modify the graphite.
[0225] Comparative Example 2:
[0226] Comparative Example 2 comprises the following steps:
[0227] 1. Preparation of boric acid modified graphite material:
[0228] 24 g of graphite raw material (natural graphite) and 2.4 g of boric acid were added to 50 mL of acetic acid, stirred, and subjected to hydrothermal reaction at 180° C. for 8 h to obtain an intermediate product;
[0229] The intermediate product was dried in an oven at 60°C, placed in a high-temperature tube furnace, introduced with 25 mL of triethylamine under a nitrogen atmosphere, heated from room temperature to 750°C within 4 hours, calcined for 5 hours, and then naturally cooled to room temperature to obtain a crude boric acid-modified graphite material;
[0230] The crude boric acid-modified graphite material is washed, dried, and ground, and then passed through a 200-mesh sieve to obtain a boric acid-modified graphite material.
[0231] 2. Preparation of negative electrode materials:
[0232] Weigh 9.5g of boric acid-modified graphite material, and fully stir and mix the boric acid-modified graphite material, conductive agent SP (conductive carbon black), and binder styrene-butadiene rubber (SBR) in a weight ratio of 95:2.5:2.5 in an appropriate amount of deionized water to form a uniform negative electrode slurry. Apply the slurry on the negative electrode current collector copper foil, dry it, and cold press it to obtain the negative electrode of Comparative Example 2;
[0233] 3. Preparation of lithium-ion batteries:
[0234] The positive electrode active material LiMn2O4, the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96:2:2, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain the positive electrode active material layer, and then cut, slit, and weld the pole ears to obtain the positive electrode.
[0235] The positive electrode, the isolation film (using a PP / PE / PP three-layer composite separator), and the negative electrode are stacked in order, so that the isolation film is between the positive electrode plate and the negative electrode plate to play an isolating role, to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and an electrolyte (containing 1 mol / L of lithium hexafluorophosphate ethylene carbonate) is injected into the bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Example 2 is completed.
[0236] The main difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, only boric acid is used to modify the graphite.
[0237] Electrochemical performance test:
[0238] Under the condition of a current density of 0.5 A / g, the specific capacity of Examples 1-7 and Comparative Examples 1-2 was detected, and the capacity retention rate after 500 cycles was calculated. The expansion rate was calculated based on the full-charge thickness of the negative electrode sheet after the lithium battery was fully charged and the initial thickness of the negative electrode sheet. The results are shown in Table 1 below.
[0239] Table 1:
[0240]
[0241] from Figure 5It can be seen that, relative to the unmodified graphite material, the boric acid-modified graphite material obtained in the present disclosure has a large number of micropores and mesopores. By comparing Examples 1-3 and Comparative Example 1, it can be seen that the modification of boric acid expands the graphite interlayer spacing, increases the number of micropores, enhances the migration rate of lithium ions, promotes the adsorption and diffusion reaction of interfacial lithium ions, maintains the integrity of the graphite negative electrode structure during the entire process of repeated charge and discharge, and improves the rate performance; and, these pores obtained after the modification of boric acid can be well used as sites for loading silicon-carbon nanoparticles, which helps to maintain the loading of silicon-carbon nanoparticles after multiple charge and discharge cycles. By comparing Examples 1-3 and Examples 4-5, it can be seen that too little or too much boric acid will affect the electrochemical performance: too little boric acid will result in fewer pores and less loaded silicon-carbon nanoparticles; and too much boric acid will result in more pores, so there are some useless gaps that are not filled by silicon-carbon nanoparticles; therefore, too little or too much boric acid will affect the electrochemical performance. Comparing Example 1 with Examples 6-7, it can be seen that the electrochemical performance of Example 1 using ZIF-67 as the first silicon-carbon material template is much better than that of Examples 6 and 7 using ZIF-90 and ZIF-8 as the first silicon-carbon material template; because silicon has obvious anisotropy during the expansion process, the reason for the anisotropy of the silicon negative electrode material expansion is the amorphous Li x Si and crystalline Si in Li + Under the action of ion flow, displacements in different directions occur. + The direction in which the dominant flow occurs coincides with the tendency of Si volume expansion along that direction; Figure 1 As shown, the first silicon-carbon material obtained in Example 1 grows axially outward from the center, and its damage to the negative electrode structure during expansion is less than that of the first silicon-carbon material obtained in Examples 6 and 7, so the expansion rate of Example 1 is significantly smaller.
[0242] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the disclosure disclosed herein. The present disclosure is intended to cover any variations, uses or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure.
Claims
1. A method for preparing a modified graphite negative electrode material for a lithium ion battery, characterized in that: The preparation method comprises the following steps: Step 1: preparing a boric acid-modified graphite material; mixing the boric acid-modified graphite material with a binder and a conductive agent to obtain a first negative electrode material; Step 2: preparing a first silicon-carbon material, applying a slurry containing the first silicon-carbon material onto the first negative electrode material, and after curing, forming a first coating on the first negative electrode material; Step 3: preparing a second silicon-carbon material, coating a slurry containing the second silicon-carbon material on the first coating layer, and after curing, forming a second coating layer on the first coating layer to obtain the modified graphite negative electrode material for a lithium-ion battery; The boric acid-modified graphite material is obtained by the following preparation method: Step 1-a: adding graphite raw material and boric acid to acetic acid, stirring and then subjecting to a hydrothermal reaction process; obtaining the product of step 1-a; Step 2-a: drying the product obtained in step 1-a, and then calcining the product to obtain a crude boric acid-modified graphite material; Step 3-a: subjecting the crude boric acid-modified graphite material to a post-treatment process to obtain the boric acid-modified graphite material; The first silicon-carbon material is obtained by the following preparation method: Step 1-b: preparing ZIF-67 material; Step 2-b: adding silicon nanoparticles to water, then adding the ZIF-67 material and glucose, stirring for 0.5-3h, and then slowly adding ethanol to obtain a dispersion; Step 3-b: leaving the dispersion to stand for 4-12 hours and then drying to obtain a first precursor; Step 4-b: subjecting the first precursor to a calcination process, and then subjecting the calcined product to acid washing to obtain the first silicon-carbon material.
2. The preparation method according to claim 1, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The hydrothermal reaction process is: the stirred acetic acid containing graphite raw material and boric acid is subjected to hydrothermal reaction at 160°C-200°C for 6-12 hours; (2) The calcination process is as follows: in a nitrogen atmosphere, triethylamine is introduced, the temperature is raised from room temperature to 650°C-850°C within 3-6 hours, calcined for 3-6 hours, and then naturally cooled to room temperature; (3) The post-treatment process is as follows: washing, drying and grinding the crude boric acid-modified graphite material, and then passing it through a 160-200 mesh sieve to obtain the boric acid-modified graphite material.
3. The preparation method according to claim 1, characterized in that: The ZIF-67 material is obtained by the following preparation method: Step 1-c: dissolving the cobalt salt and 2-methylimidazole in methanol respectively to obtain a methanol solution containing the cobalt salt and a methanol solution containing 2-methylimidazole; Step 2-c: stirring the methanol solution containing the cobalt salt, then adding the methanol solution containing 2-methylimidazole, continuing to stir for 2-6 hours, and then standing for 4-12 hours to obtain a purple solution; Step 3-c: Filter, separate, wash and dry the purple solution to obtain the ZIF-67 material.
4. The preparation method according to claim 1, characterized in that: The second silicon-carbon material is obtained by the following preparation method: Step 1-d: preparing ZIF-90 material; Step 2-d: adding silicon nanoparticles to water, then adding the ZIF-90 material and polyvinyl alcohol, stirring for 0.5-3h, and then slowly adding ethanol to obtain a dispersion; Step 3-d: leaving the dispersion to stand for 4-12 hours and then drying to obtain a second precursor; Step 4-d: subjecting the second precursor to a calcination process, and then subjecting the calcined product to acid washing to obtain the second silicon-carbon material.
5. The preparation method according to claim 4, characterized in that: The ZIF-90 material is obtained by the following preparation method: Step 1-e: dissolving the zinc salt in methanol to obtain a methanol solution containing the zinc salt, then adding trimethylamine and 2-formyl imidazole, stirring at 65° C.-80° C., and heating under reflux for 1-3 h; Step 2-e: The solution heated to reflux is further stirred at room temperature for 1-3 hours, and then water is added to obtain a precipitate; Step 3-e: The precipitate obtained in step 2-e is washed and dried to obtain the ZIF-90 material.
6. The preparation method according to claim 4 or 5, characterized in that: The preparation method satisfies at least one of the following conditions: (1) In step 2-b, the mass ratio of the ZIF-67 material to the silicon nanoparticles is selected from (0.5-0.75):1; (2) In step 2-d, the mass ratio of the ZIF-90 material to the silicon nanoparticles is selected from (0.65-0.9):1; (3) In step 2-b, the mass ratio of glucose to silicon nanoparticles is selected from (2-3.5):1; (4) In step 2-d, the mass ratio of the polyvinyl alcohol to the silicon nanoparticles is selected from (1.5-2.5):1; (5) The silicon nanoparticles have an average particle size of 75-150 nm.
7. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode material layer coated on the negative electrode current collector; the negative electrode material layer comprises a modified graphite negative electrode material obtained by the preparation method described in any one of claims 1-6.
8. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet according to claim 7.
Citation Information
Patent Citations
Modified natural graphite material as well as preparation method and application thereof
CN116314775A
Lithium ion battery silicon-containing negative plate and preparation method thereof
CN117393702A